2020
DOI: 10.1002/jnr.24613
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition reduces ventral tegmental area dopamine neuronal hyperexcitability involving AKAP150 signaling following maternal deprivation in juvenile male rats

Abstract: Traumatic early life stress (ELS) is linked to dopamine (DA) dysregulation which increases the probability of developing psychiatric disorders in adolescence and adulthood. Our prior studies demonstrated that a severe early life stressor, a 24-hr maternal deprivation (MD) in juvenile male rats, could lead to altered DA signaling from the ventral tegmental area (VTA) due to impairment of GABAergic synaptic plasticity (promoting GABAergic long-term depression, LTD) with concomitant changes in the abundance of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
1
18
1
Order By: Relevance
“…Furthermore, methylation patterns across Drd1a CpG islands significantly increased compared to age-matched control mice ( Figure 2 ) [ 79 ]. Other recent studies have reported that histone deacetylase (HDAC) inhibition reduces VTA dopamine neuronal hyperexcitability involving AKAP150 signaling following MS in juvenile male rats [ 95 , 96 ]. In this paper, the authors indicated the potential use of HDAC inhibitors as a novel class of drugs for the prevention of MS-induced dopaminergic system dysfunction [ 97 ].…”
Section: Gene Expression Alterations Induced By Msmentioning
confidence: 99%
“…Furthermore, methylation patterns across Drd1a CpG islands significantly increased compared to age-matched control mice ( Figure 2 ) [ 79 ]. Other recent studies have reported that histone deacetylase (HDAC) inhibition reduces VTA dopamine neuronal hyperexcitability involving AKAP150 signaling following MS in juvenile male rats [ 95 , 96 ]. In this paper, the authors indicated the potential use of HDAC inhibitors as a novel class of drugs for the prevention of MS-induced dopaminergic system dysfunction [ 97 ].…”
Section: Gene Expression Alterations Induced By Msmentioning
confidence: 99%
“…Additionally, MD also increased VTA DA neuronal excitability involving altered AKAP150 signaling (Shepard et al, 2020). Interestingly, administration of CI-994 (a selective class I histone deacetylase inhibitor, HDACi) recovered GABAergic plasticity, histone acetylation, BDNF abundance, (Authement et al, 2015;Shepard et al, 2018), and VTA DA excitability (Shepard et al, 2020). Indeed, transcriptional regulation of the Bdnf gene through histone modifications including deacetylation of H3K9 via HDAC2 has also been reported (Chen et al, 2003;Wang et al, 2014;Chen and Chen, 2017).…”
Section: Acetylationmentioning
confidence: 98%
“…Specifically, HDAC2 was upregulated in VTA DA neurons with concomitant decreases in acetylation at H3K9 in protein isolates harvested from VTA tissues. Additionally, MD also increased VTA DA neuronal excitability involving altered AKAP150 signaling (Shepard et al, 2020). Interestingly, administration of CI-994 (a selective class I histone deacetylase inhibitor, HDACi) recovered GABAergic plasticity, histone acetylation, BDNF abundance, (Authement et al, 2015;Shepard et al, 2018), and VTA DA excitability (Shepard et al, 2020).…”
Section: Acetylationmentioning
confidence: 99%
“…Similar to humans, in rodents the development of DAergic mesolimbic pathways seems to be largely sensitive to early life experiences ( Meaney et al, 2002 ; Brake et al, 2004 ; Peña et al, 2017 , 2019 ). The first 2 weeks of life seem to be particularly critical in rodents to shape the DAergic circuitry of the adult brain ( Gillies et al, 2014 ) and stress factors occurring early in life can induce transcriptional, structural and functional modifications in the VTA ( Chocyk et al, 2011 ; Authement et al, 2015 ; PenĂŁ et al, 2019 ; Masrouri et al, 2020 ; Shepard et al, 2020 ; Spyrka et al, 2020 ). In a nutshell, early experiences may impact the VTA and its DAergic network, thus influencing stress coping strategies and susceptibility or resilience to depression in adulthood.…”
Section: Introductionmentioning
confidence: 99%